2005
DOI: 10.1158/0008-5472.can-03-2749
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia-Induced Proteasome Inhibition and Loss of Androgen Receptor Expression in Human Prostate Cancer Cells

Abstract: Prostate cancer is the second leading cause of death in men in western countries and is usually treated by surgery and/or radiotherapy. More recently, hyperthermia has been introduced into clinical trials investigating a possible effect in the first-line treatment of prostate cancer. However, the molecular mechanisms of hyperthermia are not completely understood. In this study, we investigated the effects of hyperthermia on proteasome function and its significance for signal transduction, cell death and androg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 58 publications
7
49
0
1
Order By: Relevance
“…44 On the other hand, hyperthermia is still an angiogenesis inhibitor in the tumor treatments through decreasing the production of tumor-derived vascular endothelial growth factor. 38,39 Thus, the microvessel density in our study was decreased remarkably in tumors of combination treatment when compared with single therapy, which meant the development of angiogenesis was inhibited additionally. For these reasons, the combination treatment in our study has shown a better antitumor effect in vivo than tumor cells in vitro.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 57%
“…44 On the other hand, hyperthermia is still an angiogenesis inhibitor in the tumor treatments through decreasing the production of tumor-derived vascular endothelial growth factor. 38,39 Thus, the microvessel density in our study was decreased remarkably in tumors of combination treatment when compared with single therapy, which meant the development of angiogenesis was inhibited additionally. For these reasons, the combination treatment in our study has shown a better antitumor effect in vivo than tumor cells in vitro.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 57%
“…43 Although, not fully understood, blockade of the proteasome pathway by hyperthermia or specific blockers may also have future therapeutic values. 44 Reducing AR protein levels in CaP may become a powerful strategy in CaP treatment. 45 …”
Section: Proteasomal Degradation Of Androgen Receptormentioning
confidence: 99%
“…We have studied lipophilic derivatives of Asc including 2-ophosphoryl-6-o-palmitoyl-L-ascorbic acid (Asc2P6-Palm) and found that Asc2P6Palm was advantageous over Asc in terms of anti-metastatic activity (Liu et al 2000(Liu et al , 2003 in addition to antitumor effects Miwa et al 1988). Hyperthermia is the oldest documented tumor treatment modality (Pajonk et al 2005), and is applied in combination with chemotherapy and/or radiotherapy in the clinical setting (Takahashi et al 2002). Though the molecular mechanisms of hyperthermia are not completely understood, it is suggested that inhibition of proteosome function and the relevant signal transduction pathways might be a major factor of heat-induced apoptosis (Pajonk et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperthermia is the oldest documented tumor treatment modality (Pajonk et al 2005), and is applied in combination with chemotherapy and/or radiotherapy in the clinical setting (Takahashi et al 2002). Though the molecular mechanisms of hyperthermia are not completely understood, it is suggested that inhibition of proteosome function and the relevant signal transduction pathways might be a major factor of heat-induced apoptosis (Pajonk et al 2005). The p53-inactivated and pRb-inactivated transfectants showed G2 arrest after hyperthermia and the appearance of a sub-G1 population (van Bree et al 1999).…”
Section: Introductionmentioning
confidence: 99%